Patient-reported outcome assessment of adults and adolescents with atopic dermatitis: a cross-sectional qualitative interview study - Parima Ghafoori; Dharm S. Patel; Kimberly Raymond; Elizabeth Brennan; April Mitchell Foster; Kristi Jackson; Helen J. Birch; Wen-Hung Chen (Journal of Patient-Reported Outcomes)
Abstract Background Atopic dermatitis (AD) is a chronic inflammatory skin disease that impacts patient health and quality of life. Understanding patient experience of relevant symptoms and impacts of AD is crucial for improving outcomes. This study aimed to characterise adult (≥ 18 years) and adolescent (12–17 years) patients’ experiences of AD and assess the content validity of selected patient-reported outcomes (PROs). Methodology This non-interventional, cross-sectional, qualitative study recruited US-based, English-speaking adults and adolescents with moderate-to-severe AD, either naïve or experienced with biologics. A 90-minute interview was conducted via teleconferencing software, consisting of concept elicitation (CE) of AD experiences and cognitive debriefing (CD), where participants provided feedback on PROs assessing skin pain, sleep disturbance, and fatigue. Interview data were coded and analysed using qualitative data software to determine the AD experience and content validity of selected PROs. A conceptual disease model was developed from the CE portion of the interview. Results from the CD portion were mapped to this model to evaluate the conceptual coverage of the PROs. Results In total, 16 adults (mean age 48 years, 56% White, 63% female, 50% biologic naïve) and 20 adolescents (mean age 16 years, 60% White, 75% female, 50% biologic naïve) were included in the analysis. During CE, 13 symptoms and impacts in 7 domains were identified. The most reported symptom was itchiness (adults, 100%; adolescents, 100%) and the most reported impact was emotional functioning (adults, 94%; adolescents 95%). Participants also commonly reported experiencing pain/discomfort (adults, 69%; adolescents, 80%) and sleep disturbance (adults, 88%; adolescents, 75%). Fatigue was reported by 94% of adults across CE and CD segments. When probed during CE, 65% of adolescents identified fatigue as an impact of AD. During CD, 70–100% of participants confirmed the selected PROs were comprehensible and relevant. Conclusions This study provides evidence that the experience of AD is similar between adults and adolescents as well as biologic-naïve and biologic-experienced participants. Relevant disease concepts in patients with AD were identified, and content validity was established for the selected PROs, supporting their use in future clinical studies.